2013
DOI: 10.1099/vir.0.047506-0
|View full text |Cite
|
Sign up to set email alerts
|

Eight novel hepatitis C virus genomes reveal the changing taxonomic structure of genotype 6

Abstract: Analysis of partial hepatitis C virus sequences has revealed many novel genotype 6 variants that cannot be unambiguously classified, which obscure the distinctiveness of pre-existing subtypes. To explore this uncertainty, we obtained genomes of 98.0–98.8 % full-length for eight such variants (KM35, QC273, TV257, TV476, TV533, L349, QC271 and DH027) and characterized them using phylogenetic analyses and per cent nucleotide similarities. The former four are closely related phylogenetically to subtype 6k, TV533 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Previous studies have revealed that multiple lineages of HCV-6 are exclusively detected in Southeast Asia or among the expatriates from this region [25]. In contrast, the endemic subtypes of HCV genotypes 1, 2, and 4 have been found mainly in populations in geographically restricted areas in the sub-Saharan Africa or among African descendants in other geographic regions, but showing persistence for fewer centuries than that we here estimated for those novel Hainan variants [2629].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that multiple lineages of HCV-6 are exclusively detected in Southeast Asia or among the expatriates from this region [25]. In contrast, the endemic subtypes of HCV genotypes 1, 2, and 4 have been found mainly in populations in geographically restricted areas in the sub-Saharan Africa or among African descendants in other geographic regions, but showing persistence for fewer centuries than that we here estimated for those novel Hainan variants [2629].…”
Section: Discussionmentioning
confidence: 99%
“…Among the seven genotypes of HCV, genotype 6 (HCV 6) exhibits the highest genetic diversity [16,17]. Currently, a total of 31 subtypes, denoted 6a-6xf, are formally assigned to HCV 6, and each has at least one full-length genome determined.…”
Section: Discussionmentioning
confidence: 99%
“…Although their full-length genome sequencing is currently under completion, these variants appear to obscure the clear separation between 6a and 6b (data not shown). Unlike 6u and 6v and the ZS96 isolate, these newly identified variants were exclusively detected in Laos (Wang et al, 2013). However, due to the lack of further information for the patient from whom ZS202 was isolated, we are uncertain whether ZS202 is also epidemically linked to Laos (Gu et al, 2013).…”
Section: Discussionmentioning
confidence: 92%